2014
DOI: 10.1371/journal.pone.0095724
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Patterns of p53 and p16 and an Analysis of a Possible Role of HPV in Primary Adenocarcinoma of the Urinary Bladder

Abstract: BackgroundPrimary adenocarcinoma of the urinary bladder is rare. The molecular and cellular events leading to its pathogenesis are not well delineated. The goal of this study was to investigate p53 and p16 expression, as well as HPV status, in a relatively large series of primary bladder adenocarcinomas.Materials and MethodsThirty six cases of urinary bladder adenocarcinoma were chosen from participating institutions. The diagnosis and available clinical history were reviewed in each case. Immunostains for p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Previous studies have shown p16 expression independent of HPV infection to be associated with epithelial to mesenchymal transitions mediated by MAPK pathway (Steinestel et al, 2013). Our report is also similar to recent studies showing the possibility of p16 overexpression without HPV presence in tumours concluding that it need not always be interpreted as a defacto HPV marker (Alexander et al, 2014;Kim et al, 2014). Our results are in contrast to findings reported by Konig et al, suggesting that p16 immunostaining is to be applied as a pre-screening method for HPV subtyping and that p16 IHC correlates with high risk HPV status (Konig et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown p16 expression independent of HPV infection to be associated with epithelial to mesenchymal transitions mediated by MAPK pathway (Steinestel et al, 2013). Our report is also similar to recent studies showing the possibility of p16 overexpression without HPV presence in tumours concluding that it need not always be interpreted as a defacto HPV marker (Alexander et al, 2014;Kim et al, 2014). Our results are in contrast to findings reported by Konig et al, suggesting that p16 immunostaining is to be applied as a pre-screening method for HPV subtyping and that p16 IHC correlates with high risk HPV status (Konig et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…The use of p16 INK4A immunohistochemical analysis as a surrogate marker of HPV infection in squamous cell carcinoma of the cervix, vagina, and oropharynx has been supported by many studies in recent years [ 15 , 17 , 28 – 30 ]. The p16 INK4A expression is indicative of high risk HPV infection in cancers of squamous cell origin [ 31 ]. In our study, patients with p16 INK4A overexpression have a better prognosis, are correlated with less lymph node metastasis ( p = 0.038), and are frequently associated with lower-grade TNM stage ( p = 0.147), which are in accordance with previous studies [ 21 , 26 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, p16INK4a overexpression is common in different histological subtypes of bladder cancer including adenocarcinoma (67 %), urothelial carcinoma with squamous differentiation (45.7 %), high-grade urothelial cancers (85.9 %) and urothelial CIS (92.6 %). However, contrary to gynecological tumors, p16INK4a is not a surrogate marker for evidence of HPV infection in bladder cancer [6,[16][17][18].…”
Section: Discussionmentioning
confidence: 91%